Research progress of traditional Chinese medicine regulating intestinal flora in the treatment of hypertension - Chen, Wenjun; Xiao, Longfei; Guo, Wenlong; Li, Hailin; Chen, Rong; Duan, Zhongyu; Chen, Qinghua; Lei, Qing (Frontiers in Pharmacology, 2024)
Hypertension is a common disease; however, it is more prevalent in older adults, and its prevalence is increasing in younger populations. Numerous studies have revealed that hypertension and the composition and functionality of the intestinal flora are closely correlated. The balance of the intestinal flora, intestinal barrier integrity, and metabolite content of the intestinal flora play significant roles in the occurrence and progression of hypertension. Therefore, we performed a comprehensive review of Traditional Chinese medicine (TCM) for hypertension, focusing on the role of the intestinal flora to understand the mechanism by which TCM regulates hypertension through its effects on the intestinal flora. We analyzed the findings using the terms "traditional Chinese medicine," "hypertension," "high blood pressure," "blood pressure," "intestinal flora," "intestinal barrier function," "intestinal flora metabolites," and other keywords from the China National Knowledge Infrastructure, VIP Chinese Science and Technology, Wanfang Data, PubMed, and ScienceDirect databases. We found that TCM treats hypertension by regulating the balance of the intestinal microbiota, increasing the abundance of beneficial bacteria, reducing the abundance of harmful bacteria, improving intestinal barrier function, increasing compact proteins, reducing intestinal permeability, and regulating the content of intestinal flora metabolites. The use of TCM to treat hypertension by regulating the intestinal flora is a promising therapeutic strategy. However, most studies are limited by small sample sizes and there is a lack of large-scale randomized controlled trials. In the future, multi-center controlled clinical trials are needed to verify the efficacy and safety of TCM, optimize therapeutic protocols, and establish a foundation for the standardized and personalized application of TCM in hypertension management.